Isoscape Models of the Southern Ocean: Predicting Spatial and Temporal Variability in Carbon and Nitrogen Isotope Compositions of Particulate Organic Matter. Issue 9 (12th September 2021) - St John Glew, Katie; Espinasse, Boris; Hunt, Brian P. V.; Pakhomov, Evgeny A.; Bury, Sarah J.; Pinkerton, Matt; Nodder, Scott D.; Gutiérrez‐Rodríguez, Andres; Safi, Karl; Brown, Julie C. S.; Graham, Laura; Dunbar, Robert B.; et al.
Abstract: Polar marine ecosystems are particularly vulnerable to the effects of climate change. Warming temperatures, freshening seawater, and disruption to sea‐ice formation potentially all have cascading effects on food webs. New approaches are needed to better understand spatiotemporal interactions among biogeochemical processes at the base of Southern Ocean food webs. In marine systems, isoscapes (models of the spatial variation in the stable isotopic composition) of carbon and nitrogen have proven useful in identifying spatial variation in a range of biogeochemical processes, such as nutrient utilization by phytoplankton. Isoscapes provide a baseline for interpreting stable isotope compositions of higher trophic level animals in movement, migration, and diet research. Here, we produce carbon and nitrogen isoscapes across the entire Southern Ocean (>40°S) using surface particulate organic matter isotope data, collected over the past 50 years. We use Integrated Nested Laplace Approximation‐based approaches to predict mean annual isoscapes and four seasonal isoscapes using a suite of environmental data as predictor variables. Clear spatial gradients in δ 13 C and δ 15 N values were predicted across the Southern Ocean, consistent with previous statistical and mechanistic views of isotopic variability in this region. We identify strong seasonal variability in both carbon and nitrogen isoscapes, with key implications for the use of static or annual average isoscape baselines in animal studies attempting to document seasonal migratory or foraging behaviors. Key Points: First carbon and nitrogen isoscape predictions of the entire Southern Ocean, based on particulate organic matter isotope data Clear spatial gradients in δ 13 C and δ 15 N values were predicted, consistent with previously reported isotopic variability in this region Key implications for the use of isoscape baselines in animal studies attempting to document seasonal migratory or foraging behaviors